The relation among ramal width and length with some cervical and cranio-facial measurements in different skeletal classes - Esraa S Jassim (College of Dentistry/ University of Baghdad, 2014)
Background: The purpose of this study was to assess the relation among the ramal length and width with various cervical and cranio-facial measurements for a sample of Iraqi adults with different skeletal classes. Materials and method: The sample composed of 71 Iraqi adults (36 females and 35 males) with an age ranged between 17-30 years and had different skeletal mal-relations using SNA, SNB and ANB to differentiate between them and assorting them into CL.I, CL.II and CL.III mal-relation. Each individual was subjected to clinical examination and digital true lateral cephalometric radiograph that had been analyzed using AutoCAD 2007 software computer program to determine sixteen linear and ten angular measurements. Descriptive statistics were obtained and independent samples t-test was performed to evaluate the gender differences in different classes. ANOVA test as used to compare the measurements among the skeletal classes in each gender, while Pearson's correlation coefficient test was used to determine the relations among ramal length and width with other measurements in all classes. Results and Conclusions: All of the linear measurements were significantly higher in males than females. On the other hand, the angular measurements showed non-significant gender difference except for SN-PP angle in class II group. ANOVA test showed statistically significant difference in upper gonial angle, Y-axis angle and the mandibular length. Ramal length and width correlated significantly with PFH, SN-MP angle and Co-Gn.